Os calunzeiros: quilombos e as construções da liberdade no sertão do São Francisco. - Silva, Johnisson Xavier (2021)
My objective, in this thesis, is to analyze the formation, forms of occupation and permanence, social dynamics, work, religiosity, cultural practices and the meanings of the quilombola’s territories in the North of Minas Gerais, in the Sertão do São Francisco, in the last decades of the 19th century and in the 20th century. I aim to fill the gaps and the historical silences about the life and trajectory of the black communities of the region. I adopt, as a presupposition, the conception that the black people territories in the North of Minas Gerais constituted through migratory groups coming mainly from Bahia (scaping from slavery, as well as through other migratory processes) since they found, in the waterways and through the thick woods of the land, paths to build freedom. The window through which I choose to view and cover the history of the quilombo residents in the North of Minas is the city of Januária, more precisely the quilombo of the Calunzeiros, located in the district of Riacho da Cruz. I opted for this geographical section due to the centrality that the city exercised until the first half of the twentieth century in the region, being a mandatory route of the slave trade. A range of black people’s territories developed around the city, distributed by neighboring districts and towns. The research makes use of what Flávio Gomes (1996) called “black field”, as well as the game of scales and methodological proposals of microhistory to account for the established objectives. Thus, when dealing with the Calunzeiros, historical narratives, also of the Black People in the Sertão do São Francisco, are built. To this end, I use the speech of travelers, their orality, parish registers and documents, letters, reports, memorials, and phonographic records.